The Attitudes of Faculty Members of Ahwaz Jondishapour University of Medical Sciences toward Student Advising and Counseling - Pourandokht Asadollahi; Abdolhussein Shakurnia; Hossein Elhampour (Kerman University of Medical Sciences, 2011)
Background and Objective: One of the professional duties of university faculty members is student counseling T he aim of this study was to determine the attitudes of faculty members toward advising and counseling students in Ahwaz Jundishapur University of Medical Sciences (AJUMS) Methods: In this descriptive crosssectional study the attitudes of 114 faculty members toward students counseling were investigated using a 34item questionnaire applying 5point Likert scale The validity and reliability of the questionnaire had been confirmed through a pilot study Data were analyzed through SPSS software using mean and chi square test Results: Fifty seven percent of the faculty members participated in the study was females with teaching experience of 1485±88 years Faculty members asserted that they are interested in students counseling (mean score: 412 out of 5) but have moderate knowledge about the advisory task (mean: 361) Mean total score of the present statues of students counseling in the university was 338±056 and that of the ideal situation was 405±038 (p=0001) Conclusion: It is concluded that faculties have a positive attitude toward the importance and necessity of student counseling but believe that the implementation of this process is not properly monitored and supported in AJUMS Support of advisory teachers and more attention to their statues can be very beneficial in the process of students counseling